Acute intestinal obstruction due to appendicular tie syndrome: a rare case report - Agrawal, Akash; Vora, Palak (International Surgery Journal, 2019)
Acute intestinal obstruction is one of the most common surgical emergencies encountered by surgeons on daily bases. Most common causes for small bowel obstruction includes postoperative adhesions and hernia. One of the rarest cause of intestinal obstruction is appendicular band syndrome. Here we report a case of small bowel obstruction due to appendicular tie syndrome in a 70 years old male patient at GMERS hospital, Dharpur, Patan, Gujarat, India.